Open data: Are new gender-neutral pronouns difficult to process in reading? The case of hen in Swedish - Hellen Vergoossen (Stockholm University, 2020)
The raw data, preprocessing script, preprocessed data file, and the main analyses for the project "Are new gender-neutral pronouns difficult to process in reading? The case of hen in Swedish".
The psychopy data set includes measures of key press responses to comprehension questions recorded during the experiment. It also includes information on in what order the stimuli were displayed to the participant, and how much time they spent looking at the stimulus until they pressed a key to move on to the next stimulus.
The questionnaire data set includes background information collected through the online questionnaire designing webpage Qualtrics (https://qualtrics.com) after the eye-tracking experiment. Data was collected between Sept 25th 2017 and March 8th 2018.
The eye-tracking data set includes measures of reading behaviors such as fixation time on stimuli including gendered and gender-neutral pronouns.
Instrument- or software-specific information needed to run the experiment and interpret the data:
Psychopy (Peirce et al., 2019) for running the experiment (https://www.psychopy.org/). Python for opening and managing the related .py files (https://www.python.org).

BeGaze (SensoMotoric Instruments, 2014) for opening and managing the .idf files. Requires software license. These files were created using SMI's software iView for recording eye movements with the eye-tracker.[https://gazeintelligence.com/smi-software-download]
Rstudio used with R (R Core Team, 2017): https://rstudio.com/products/rstudio/
More information can be found in the README files, and on our OSF page.
Keywords: Personality, Social and Criminal Psychology; 200405 Language in Culture and Society (Sociolinguistics); Psychology; Psykologi